Embedding gamification approach in education / Haslinda Noradzan ... [et al.] - Noradzan, Haslinda; Ahmad Zaini, Azniza; Abdul Rahman, Rozeleenda; Hussin, Adibah; Abd Aziz, Mohd Norafizal (UiTM Press, 2019)
The process of memorizing too many terminologies and technical facts for most of courses can be difficult for students and lecturers as it requires students to recognize and comprehend the concepts very well. It has become a big challenge for both students and lecturers to achieve the same learning outcomes of the courses as different students have different learning styles and preferences. Hence, this chapter is written purposely to reviews the previous studies in exploring the current teaching and learning practices that embraced the gamification approach in education. This chapter also discovered the features of gamification to be considered by the lecturers for ensuring the gamified activities and products designed are suitable to be used in educational environment. Also discussed and explored in this chapter are the advantages of embedding gamification elements in teaching and learning environment.